Differential structure of values among three educational generations in Bangladesh - Ara, Shawkat; Kabir, Balaka; Samad, Syeda Shahria; Ahmed, Rasel (Rajshahi University Journal of Life & Earth and Agricultural Sciences, 2015)
The present study was conducted to investigate the differential structural properties of values among the three educational generations in Bangladesh. Underlying conviction of the present study was that certain specific patterns of values are modelled by the history, culture and socio-economic condition of a particular nation in which it is exposed. It was predicted that certain value pattern have different implication in different educational generation having unique experienced and pattern of its own. The sample of the study was composed of 180 Ss equally divided into older teachers, younger teachers and students in different educational institutions of Rajshahi town in Bangladesh (N = 60) for each group separately. Age of the older teachers ranged from 45 to 60 years, younger teachers ranged from 31 to 40 years and students ranged from 20 to 29 years. The data were obtained through Rokeachs value inventory (Aras Bengali version). These data were factor analyzed by using Kaisers criterion of oblique rotation method. Six factors extracted through factor analysis for older teachers, six factors for younger teachers and seven factors for students revealed the differential structural properties of values. These findings supported the conviction that differential value pattern of three generations stemming from the present political, economic, cultural situation may exert enormous influence on the differential educational institutions causing three different pattern of values.